Peculiarities of a Distant Learning Model of an Educational Portal - Y.G. Yakusevich (Ìнформаційні технології в освіті)
Peculiarities of specific features the conditions of the distantion education, the conditions of the optimum computer technologies, that effect an effectiveness in the formation of an indicator of knowledges are developed.